Keran Air Otomatis Pada Bak Mandi Berbasis Arduino Uno Menggunakan Sensor Ultrasonic - Suhardi Suhardi (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Water is one of life's resources for all living things. However, at this time the available net amount is very limited. Efforts that can be done is to utilize the best possible air. One of them by regulating the air bath by controlling the level of air in the air shelter. In this final task used an automatic faucet using ultrasonic sensor is a sensor that will detect the object and remove or turn off the air automatically with the main driving media using servo motors. In the filling of an air-conditioning tub to prevent overflow of ultrasonic sensors which will automatically charge when the air volume distance does not match the specified and will also automatically charge at the same time. No more air is wasted due to user negligence. Keywords :Faucet, Arduino, Ultrasonic